Comparison of the Effectiveness of Perinatal Yoga and Relaxation Techniques in Reducing Pain in Third Trimester Pregnant Women at the Bongo II Community Health Centre - Maya Novitasari; Tut Rayani Aksohini Wijayanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Pain is a prevalent issue frequently seen by pregnant women in their third trimester, attributable to physiological, biomechanical, and psychological alterations during gestation. Non-pharmacological pain management is essential as a secure alternative to enhance the comfort of pregnant women. Perinatal Yoga and Relaxation Techniques are two commonly endorsed non-pharmacological therapies; yet, comparative analyses of their efficacy remain scarce, particularly within primary health care settings. This study is to evaluate the efficacy of Perinatal Yoga against Relaxation Techniques in alleviating pain among pregnant women in their third trimester at the Bongo II Community Health Centre. The research employed a quasi-experimental design with a two-group pretest-posttest methodology. The sample comprised 38 pregnant women in their third trimester, categorized into two groups: 19 participants in the Perinatal Yoga group and 19 participants in the Relaxation Techniques group. The Numeric Rating Scale (NRS) was utilized to assess pain severity prior to and following the intervention. A paired t-test was utilized for intra-group differences, whereas an independent t-test was employed to assess inter-group efficacy.The findings indicated that both Perinatal Yoga and Relaxation Techniques markedly diminished pain intensity in pregnant women throughout their third trimester (p<0.001). The decrease in pain in the Perinatal Yoga group was statistically significant compared to the Relaxation Technique group (p<0.05). This study concludes that Perinatal Yoga is superior than Relaxation Techniques in alleviating pain in pregnant women during their third trimester. Perinatal Yoga is indicated as an effective and practical non-pharmacological technique in antenatal treatment inside primary health facilities.